(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Cypermethrin is a potent pyrethroids insecticide causing different pathological features when exposed to mammal. Vitamins are used as nutrient supplements and in clinical studies as medical intervention in some disease conditions. This study was designed to investigate the possible protective effect of vitamin C and E on Cypermethrin induced nephrotoxicity in wistar albino rats. Twenty-eight (28) wistar albino rats were sorted into four groups of seven rats per groups were used in this study. Group A serves as the control and received distilled water orally. Group B, C and D were administered 25mg/kg body weight cypermethrin orally. Group C and D were treated daily with 40mg/kg body weight vitamin C and 20mg/kg body weight vitamin E respectively by oral administration while group B was left untreated for 14 days. Cypermethrin significantly (P<0.05) induced nephrotoxicity as characterized with significant increased (P<0.05) in the serum levels of Urea, uric acid and creatinine. It also caused significant decrease (P<0.05) in renal total protein, albumin and globulin. Exposure to Cypermethrin induced electrolyte imbalance in rats with significant increase in serum chloride ion, potassium ion and significant decrease in serum level of sodium ion and bicarbonates. Histological results revealed that cypermethrin caused distortion in histoarchitecture of the kidney characterized by lesion of glomerulus, damaged Bowman’s capsule, degenerated and vacuolated renal tubules. Taken together, vitamin C and E significantly reverse all these alterations and offer protection to the kidney membrane.